The Effect of Bilingual Student Worksheet Application toward Students Learning Outcomes on the Human Reproductive System Topic - Hardianti, Yulia; Sartono, Nurmasari; Dewahrani, Yulilina Retno (Universitas Negeri Jakarta, 2014)
The aim of this research was to know the effect of the use of bilingual student worksheet toward students learning outcomes on the human reproductive system topic. This research was conducted at SMAN 68 Jakarta on April-May 2012. The method was quasi-experimental with posttest-only design. The Simple random sampling technique selected 30 students grade 11 of IPA 4 included in experimental group and another 30 students grade 11 of IPA 3 as control group. This research used instrument of multiple choice test with five alternative answers. Prerequisite Testing for normality of Kolmogorov Smirnov and homogeneity testing of F-test showed a normal distribution and homogenous data. The hypothesis testing on cognitive learning result using t-test at Î± = 0.05 indicated that tcount (2.35) > ttable (2.00) which rejected the H0, whether the hypothesis testing on affective learning result using t-test at Î± = 0.05 showed that t count (3.84) > t table (2.00) which rejected the H0. Based on the results, it can be concluded that there was an effect of using the bilingual student worksheet toward students learning outcomes on the human reproductive system topic.